2020
DOI: 10.3389/fnagi.2020.594810
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Age-Related Changes in Precise Grip Force Regulation: A Combined EEG-fNIRS Study

Abstract: Motor control is associated with suppression of oscillatory activity in alpha (8–12 Hz) and beta (12–30 Hz) ranges and elevation of oxygenated hemoglobin levels in motor-cortical areas. Aging leads to changes in oscillatory and hemodynamic brain activity and impairments in motor control. However, the relationship between age-related changes in motor control and brain activity is not yet fully understood. Therefore, this study aimed to investigate age-related and task-complexity-related changes in grip force co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…However, clustering co‐occurrences of words and how they relate provided the possibility to predict the newest tendencies and the future of fNIRS. For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, 124–127 social and emotional engagement, 128–130 BCI systems, 63,64 and rehabilitation 131 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, clustering co‐occurrences of words and how they relate provided the possibility to predict the newest tendencies and the future of fNIRS. For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, 124–127 social and emotional engagement, 128–130 BCI systems, 63,64 and rehabilitation 131 …”
Section: Discussionmentioning
confidence: 99%
“…For example, in the last year, authors dedicated their attention to cognitive functions and motor impairment, 56,58,122,123 development and language, [124][125][126][127] social and emotional engagement, [128][129][130] BCI systems, 63,64 and rehabilitation. 131 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It consistently indicates that, in general, individuals over the age of 60 tend to apply greater grip force than young adults [2]. Despite this general trend, EEG analysis demonstrated that the specific neural processes and cortical activations associated with grip force among the older population can vary depending on the task being performed [16,20]. This implies that the association between the grip force coordination and neural activity varies across different activities.…”
Section: Introductionmentioning
confidence: 99%